Does greater food safety consciousness benefit smallholder dairy farmers? Evidence from Nepal - Thapa, Ganesh B.; Kumar, Anjani; Roy, Devesh; Joshi, Pramod Kumar (International Food Policy Research Institute, 2019)
Food quality and safety have been the central issues of food economics and are considered among the most important food attributes. However, evidence of the impact of food safety consciousness on consumers' food purchasing behavior is limited. This paper studies the impact of food safety consciousness on weekly milk expenditure, milk price paid, milk quantity purchased, and the probability of purchasing milk from modern market outlets in Nepal. We conducted dairy consumer survey in four selected districts of the country and employed an instrumental variable regression and quantile instrumental variable to estimate the heterogeneous treatment effects. The results suggest that education, income, and social network are the major factors that positively influence food safety consciousness. An increase in the food safety consciousness level by 1% increases the weekly milk expenditure, milk price paid, and weekly milk purchased by 1.37%, 0.66%, and 1.27%, respectively. Furthermore, we found that an increase in food safety consciousness by 1% is associated with a 37% higher probability of selecting a modern milk outlet. At higher levels of food safety consciousness, female-headed households are significantly more likely to purchase milk from modern outlets in comparison to male-headed households. Our findings imply that increasing food safety consciousness is likely to improve food security (through more consumption of milk and other healthy food) and the welfare of smallholder dairy farmers (through increased milk demand and higher milk prices paid by consumers).